2016
DOI: 10.1093/nar/gkw052
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Sequence Variation on Genome-wide NRF2 Binding—New Target Genes and Regulatory SNPs

Abstract: Transcription factor binding specificity is crucial for proper target gene regulation. Motif discovery algorithms identify the main features of the binding patterns, but the accuracy on the lower affinity sites is often poor. Nuclear factor E2-related factor 2 (NRF2) is a ubiquitous redox-activated transcription factor having a key protective role against endogenous and exogenous oxidant and electrophile stress. Herein, we decipher the effects of sequence variation on the DNA binding sequence of NRF2, in order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 72 publications
2
44
0
2
Order By: Relevance
“…According to the GWAS catalog (http://www.ebi.ac.uk/gwas/), six SNPs (rs9533090, rs9594738, rs17638544, rs8001611, rs9533095, and rs9594759) at 13q14.11 have been reported by previous GWASs on osteoporosis . These SNPs were located in the intergenic region close to AKAP11 (∼65 kb) and distal from RANKL (∼185 kb).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the GWAS catalog (http://www.ebi.ac.uk/gwas/), six SNPs (rs9533090, rs9594738, rs17638544, rs8001611, rs9533095, and rs9594759) at 13q14.11 have been reported by previous GWASs on osteoporosis . These SNPs were located in the intergenic region close to AKAP11 (∼65 kb) and distal from RANKL (∼185 kb).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple intergenic SNPs at 13q14.11 have been reported by previous GWASs on osteoporosis . Deciphering the functional mechanisms of how these noncoding SNPs influence osteoporosis risk is critical to help translate GWAS findings into clinically useful information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-126 is encoded in the seventh intron of the gene for the endothelial-specific protein epidermal growth factor-like domain 7 (Egfl7) and its expression is partially (~30%) dependent on transcription factors that bind to the promoter region of this Egfl7 [93]. Additionally, miR-126 expression is regulated, independently of Egfl7, by the DNA methylation status of a miR-126-specific promoter located in intron 7 of Egfl7 [94], as well as the binding of Nrf2 to this region in response to oxidative stress [95]. Preliminary data from our group show that FGR human endothelial cells present increased levels of DNA methylation in miR-126 promoter, suggesting an epigenetic programming of this miRNA in FGR endothelium.…”
Section: Potential Role Of Hypoxia-induced Mirnas Mir-21 and Mir-126mentioning
confidence: 99%
“…Mutations in TF binding sites, including point mutations and indels, can explain a substantial portion but not all of the binding divergence. [25][26][27] Despite the dramatic turnover of individual TF binding, Ballester et al found that about 2-thirds of TF binding sites were located within cis-regulatory modules (CRMs), although less than half of the CRMs in humans were also CRMs in other species, 28 suggesting some degree of coevolution of different TF binding.…”
mentioning
confidence: 99%